Role of Water in Decarbonizing Construction Sector: A Life Cycle Perspective - Tahir Furqan; Al-Ghamdi Sami G. (E3S Web of Conferences, 2025)
Buildings are widely acknowledged as one of the most significant uses of freshwater resources on a global scale. The massive use of construction and operational water depletes water supplies and has a significant environmental impact. The energy-intensive water cycle in built environments—covering raw water treatment, distribution, consumption, and wastewater treatment—further aggravates this issue. In the Gulf region, renewable water resources are below survival thresholds, increasing reliance on desalination to meet growing demands. However, desalination requires substantial energy and resources, posing environmental, economic, and social challenges. This study considers the environmental impacts of of water use in construction water. For this purpose, life cycle assessment (LCA) was employed to assess the carbon and water footprints for concrete and steel usage. It was found that implementing greywater reuse in construction sector significantly reduces carbon footprints and other environmental impacts. The findings highlight the need for region-specific building rating systems (e.g., LEED) that incorporate water conservation criteria. Additionally, enhancing desalination efficiency through national research initiatives can substantially lower building water use. These insights can inform policymakers in developing sustainable water strategies to mitigate environmental impacts.